Controle dos gastos públicos no Brasil após a EC 95/2016: reflexões sobre a constitucionalidade do novo Regime Fiscal. - Vasconcelos Filho, José Aécio (2019)
The acute fiscal imbalance faced by Brazil especially since the last decade served as a backdrop for the issuance of Constitutional Amendment nº. 95/2016, which established the Novo Regime Fiscal (NRF), prohibiting the real growth of primary expenditure of all federal autonomous departments. Following the fiscal responsibility guideline adopted by the Federal Government, many subnational entities have instituted similar rules, also limiting the growth of primary expenditure at the level of states. In establishing a ceiling for public spending, the Novo Regime Fiscal made it impossible to comply with other constitutional rules, such as those that oblige the Federal Government to execute a minimum percentage of its tax collection in actions related to health and education. This paper aims to study, from a constitutional perspective, the main instruments used by Brazil in controlling the expansion of public spending and the increase in public debt, especially the Novo Regime Fiscal. The objective will not be to examine whether the option to reduce the debt from the generation of primary surplus is adequate for the economic and social reality of Brazil, but only to verify if the instrument used by the reforming constituent is compatible with the Federal Constitution. Specific objectives include: a) analysis of the reasons why government officials find it difficult to control the expansion of public spending in the country, even though the adverse effects of high debt are known; b) examination of the effectiveness of the fiscal management instruments provided for in the Federal Constitution and in the Lei de Responsabilidade Fiscal; c) the study of the functioning of the public spending ceiling in other countries; d) verification of the main similarities and differences between the Novo Regime Fiscal and the subnational constitutional amendments that limited the growth of the expenses at the level of states and e) the analysis of the compatibility of the rules of the NRF with the Constitution. The methodology used was documental and bibliographical, focusing on the analysis of the doctrine and jurisprudence of the Federal Supreme Court. The survey indicated that while some fiscal rules (such as the ‘golden rule’, for example) were always obeyed, many other rules were ignored or met only formally. The study of the functioning of the public expenditure ceiling in other countries indicated that this mechanism varies according to the peculiarities of each nation, but it was possible to observe that most of the studied countries restrict the growth of the public debt, and not of the primary expenditure. The comparison of the provisions of the Novo Regime Fiscal with our constitutional reality allowed us to conclude that EC 95/2016 did not violate the Constitution, since it did not confront the essential core of social rights such as education and health, which may even be expanded and improved if there is a more rational debate on efficient allocation of available resources. There was also no violation of the separation of powers, since the new fiscal management instrument imposed budgetary restrictions identical to all autonomous federal departments. Finally, the rigidity of the Constitutional Amendment nº. 95/2016, which prohibits the real growth of primary expenditure by at least ten years, did not violate the democratic principle, since the rule was legitimately approved by the National Congress, the same institution that may change it at any time if it considers that it did not meet the objective it proposes. The research also concluded that the institution of the expenditure rule, although constitutional, is not enough to solve the fiscal imbalance situation faced by Brazil. The solution of the problem also involves the effective obedience to the rules of the Lei de Responsabilidade Fiscal, with the consequent abandonment of hermeneutical maneuvers constructed with the purpose of making fiscal rules more flexible.